Value Education Through the Learning of the Book of Ta'lim Al-Muta'allim in Strengthening Student Religious Behavior (Case Study in Intensive IDIA Prenduan Sumenep 2023) - Ruslan; Syafrudin Muhammad (Penerbit Hellow Pustaka, 2024)
The Ta'lim al-Muta'allim book is a book that discusses the manners of students to seek knowledge as the key to success in learning. The book also mentions various provisions that must be owned by students and are often brought on their journey to seek knowledge so that students can achieve their goals, namely gaining useful and blessed knowledge. So learning the Ta'lim Al-muta'allim book aims to provide guidance to students to achieve useful knowledge and can be developed independently so that it is useful for other humans. Basically, education that emphasizes improving student morals. The method used in this study is a qualitative approach and a descriptive type of research. The location of the research is at Ma'had IDIA Prenduan, while the data collection technique uses interviews, observations, and documentation. And using the technique of checking the validity of data with data triangulation then the data that has been obtained is analyzed using data reduction techniques, data presentation and drawing conclusions. To find out how the value learning contained in the Ta'lim Al-muta'allim book is implemented, the researcher tries to thoroughly examine the value learning contained in the Ta'lim Al-muta'allim book which is implemented in Ma'had IDIA Prenduan. With the hope that the results of this study can be useful for all IDIA Prenduan students and all communities. So from the results of the research conducted by the researcher at Ma'had IDIA Prenduan, it is aware of the importance of value learning contained in the Ta'lim Al-muta'allim book in an education system that exists in the institution so that students are able to implement the contents of the Ta'lim Al-muta'allim book so that they can be applied in everyday life in accordance with the teachings taught by Imam Az-Zarnuji (Ta'lim Al-muta'allim).